2013
DOI: 10.18267/j.efaj.104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internally Generated Intangible Assets on Financial Statements Prepared in Accordance with IFRS

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Even though the IAS 38 imposes the capitalization of development expenditures if specific requirements are met, companies can exercise judgments to distinguish between research and development phases and assess the commercial viability and technical feasibility of the outcomes. Also, the assessment of the fulfilment of requirements is under the estimation of managers (Vašek, Filinger, 2013). Fuentes and Persson (2011) found that Swedish listed companies capitalize R&D to smooth earnings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Even though the IAS 38 imposes the capitalization of development expenditures if specific requirements are met, companies can exercise judgments to distinguish between research and development phases and assess the commercial viability and technical feasibility of the outcomes. Also, the assessment of the fulfilment of requirements is under the estimation of managers (Vašek, Filinger, 2013). Fuentes and Persson (2011) found that Swedish listed companies capitalize R&D to smooth earnings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Corporate intangible assets can be either purchased (individually or as part of a business combination) or internally generated (Vašek & Filinger, 2013). Goodwill is an intangible asset that is typically paid for in a business combination when the consideration paid to acquire the target company exceeds the fair value of the target's net assets (Robinson, Henry, Pirie, & Broihahn, 2012).…”
Section: Introductionmentioning
confidence: 99%